Carbon sink potential of the Philippine mangrove forest - Gevaña, Dixon T.; Im, Sangjun (2011)
The importance of mangrove for both human and coastal organisms has been well-documented in many literatures. Among which is the capacity to trap atmospheric carbon into its biomass and help mitigate the impacts of climate change such as tidal surge, erosion and salt water intrusion. Notwithstanding its smaller share in the global forest cover, it is one of the most productive and biodiverse ecosystems. On the average, mangrove contains as much as much as half of the old growth forest biomass, represents 12 genera of plants. The Philippine mangrove forest currently accounts to 247,362 ha, and is gradually increasing because of the coastal rehabilitation programs being implemented by the government, NGOS and communities. Mangrove trees are very common in almost all coastal areas of the country. All regions, except the Cordillera Autonomous Region (CAR) harbour mangrove forest. Among the regions MIMAROPA (Region 4B) has the largest share with 57,567 ha, followed by ARMM in Mindanao with 45,786 ha, and Region 8 (Samar and Leyte) with 38,781 ha. To estimate the potential of Philippine mangrove for carbon storage, carbon density estimates observed by the Environmental Forestry Programme of the University of the Philippines Los Baños were used. On the average, the country’s mangrove could be storing as much as 28.56 to 35.05 megaton carbon (Mt C). Among the provinces, Palawan (53,678 ha) and Sulu (24,305 ha) have the largest carbon stocks with 6 to 7 Mt and 3 to 3.5 Mt, respectively. Indeed, Philippine mangrove has huge potential for carbon storage hence proper forest management is vital to sustain its ecological roles.
Keywords: Mangrove forests; Carbon; Climate change; Forest conservation; Mangrove conservation